Air pollution tolerance index (APTI) and antioxidant potentials using DPPH assay of mature leaves from selected tree species llong Intramuros Walls, Manila - Damaso, Russel Jan S., Del Carmen, Kirk Patrick F., Mercado, Alessandra P., Olarte, Princess M., Ponpon, Jerona Mae M. 4 0 16; 5
ABSTRACT: The primary objective of this study is to determine the Air Pollution Tolerance Index (APTI) and antioxidant potential of Artocarpus heterophyllus, Mangifera indica, Monoon longifolium, and Syzygium cumini in an environment marked by elevated air pollution levels-Intramuros, Manila. Additionally, the study aims to explore any correlation between pollution tolerance and the capacity to mitigate oxidative stress, which serves as an indicator of antioxidant potential in these species. The findings of this study offer valuable insights for diverse fields, including environmental management, public health, and biodiversity conservation. Plants defend themselves against air pollution-induced harm through their antioxidant systems, comprising compounds like phenolics, flavonoids, carotenoids, and antioxidant enzymes. These elements counteract Reactive Oxygen Species (ROS) generated by air pollutants, thus imparting pollution tolerance. This study assessed APTI values based on parameters such as ascorbic acid content, total chlorophyll, leaf extract pH, and relative water content. Additionally, phytochemical analysis was conducted to determine the presence of antioxidative compounds in each species, followed by the evaluation of antioxidant potential using the DPPH radical scavenging assay. Results demonstrated varying degrees of pollution tolerance among the tree species, with S. cumini categorized as Immediately Tolerant, and the others as Tolerant. Regarding antioxidant potential, M. longifolium exhibited the highest activity, trailed by M. indica, A. heterophyllus, and S. cumini. Statistical analysis indicated an absence of significant correlation between APTI and antioxidant potential, highlighting that APTI alone cannot reliably predict the antioxidant potential of plant species.
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2